Analisis Implementasi Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) - Syaifur Rahman; Sugeng Hartanto; Avisenna Harkat (Jurnal Akuntansi Terapan dan Bisnis, 2023)
The purpose of this study was to analyze the implementation of the Institutional Level Financial Application System (SAKTI) at the Semarang I State Treasury Service Office. This research is a qualitative research with a case study approach. Data collection was carried out by interview, observation, and documentation techniques. The selection of informants is based on certain criteria, namely by selecting KPPN employees who act as users or users of SAKTI. Selection is based on employee knowledge and understanding in using the SAKTI application. In accordance with the provisions of the Regulation of the Minister of Finance of the Republic of Indonesia Number 171/PMK.05/2021 concerning Implementation of the SAKTI System. The results of the study indicate that the application of the SAKTI application at the Semarang I KPPN has been implemented well and has brought many positive influences and is very supportive of all activities, main tasks and functions of the KPPN.